2012
DOI: 10.1186/1746-6148-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of the intestinal phosphate binder Lantharenol® in cats

Abstract: BackgroundTolerability and efficacy of the intestinal phosphate binder Lantharenol® (lanthanum carbonate octahydrate) were tested in two prospective, randomized and negative controlled laboratory studies with healthy adult cats fed commercial maintenance diets non-restricted in phosphorus. In the first study, the maximal tolerated dose was determined. Starting from a dose of 0.125 g/kg body weight mixed with the daily feed ration, the dose of Lantharenol® was doubled every other week until signs of intolerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Lantharenol ® , a noncalcium‐based phosphate‐binding food additive, was given as described for uraemic cats . This is one of the treatment strategies in calciphylactic human patients with hyperphosphataemia .…”
Section: Discussionmentioning
confidence: 99%
“…Lantharenol ® , a noncalcium‐based phosphate‐binding food additive, was given as described for uraemic cats . This is one of the treatment strategies in calciphylactic human patients with hyperphosphataemia .…”
Section: Discussionmentioning
confidence: 99%
“…Several agents can be used for this purpose (see Table 4). 53,[67][68][69] There are no studies comparing different phosphate binders in cats with CKd, but all are likely to be efficacious. 53 offering alternative binders when needed may be appropriate, as palatability of the phosphate binders varies.…”
Section: Use Of Phosphate Bindersmentioning
confidence: 99%
“…From the literature search performed (see also paragraph under Section 3.2), only four scientific papers were chosen as being potentially relevant to the safety assessment. The FEEDAP Panel considered these four papers and found that one of them (Schmidt et al, 2012) in an unpublished formhad been already assessed in the previous application. The other three papers (DiBartola, 2010;Thom et al, 2013;Bernachon et al, 2014) did not provide any relevant additional information on the safety of the product when used for cats.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%